Mechanically Defined Microenvironment Promotes Stabilization of Microvasculature, Which Correlates with the Enrichment of a Novel Piezo‐1+ Population of Circulating CD11b+/CD115+ Monocytes. Issue 21 (29th March 2019) - Forget, Aurelien; Gianni‐Barrera, Roberto; Uccelli, Andrea; Sarem, Melika; Kohler, Esther; Fogli, Barbara; Muraro, Manuele G.; Bichet, Sandrine; Aumann, Konrad; Banfi, Andrea; Shastri, V. Prasad
Abstract: Vascularization is a critical step in the restoration of cellular homeostasis. Several strategies including localized growth factor delivery, endothelial progenitor cells, genetically engineered cells, gene therapy, and prevascularized implants have been explored to promote revascularization. But, long‐term stabilization of newly induced vessels remains a challenge. It has been shown that fibroblasts and mesenchymal stem cells can stabilize newly induced vessels. However, whether an injected biomaterial alone can serve as an instructive environment for angiogenesis remains to be elucidated. It is reported here that appropriate vascular branching, and long‐term stabilization can be promoted simply by implanting a hydrogel with stiffness matching that of fibrin clot. A unique subpopulation of circulating CD11b + myeloid and CD11b + /CD115 + monocytes that express the stretch activated cation channel Piezo‐1, which is enriched prominently in the clot‐like hydrogel, is identified. These findings offer evidence for a mechanobiology paradigm in angiogenesis involving an interplay between mechanosensitive circulating cells and mechanics of tissue microenvironment. Abstract : Neovasculature is vital for tissue repair and regeneration. In this study, the induction and stabilization of blood vessels by simply injecting a biomaterial of defined mechanical properties is reported. A hitherto unknown population of circulating monocytes positive for mechanosensing protein Piezo‐1, which is recruited de novo in vessel maturation, is identified, thus elaborating a role for mechanobiology in vascular stabilization.